2014
DOI: 10.1371/journal.pone.0104016
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose X-Ray Irradiation Promotes Osteoblast Proliferation, Differentiation and Fracture Healing

Abstract: Great controversy exists regarding the biologic responses of osteoblasts to X-ray irradiation, and the mechanisms are poorly understood. In this study, the biological effects of low-dose radiation on stimulating osteoblast proliferation, differentiation and fracture healing were identified using in vitro cell culture and in vivo animal studies. First, low-dose (0.5 Gy) X-ray irradiation induced the cell viability and proliferation of MC3T3-E1 cells. However, high-dose (5 Gy) X-ray irradiation inhibited the via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 37 publications
5
55
0
Order By: Relevance
“…A remarkably increased incidence of delayed and nonunion fracture within a prior irradiated bone has been a well‐known clinical observation for many years. Several previous rodent studies reported that radiation before or immediately after fracture causes alterations in the histology and radiology of the reparative processes . However, all those studies used whole‐body radiation, which limited the local radiation dosage that could be applied and was always accompanied by systematic effects, which primarily affect hematopoiesis and had abscopal effects on radiation‐shielded bones .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A remarkably increased incidence of delayed and nonunion fracture within a prior irradiated bone has been a well‐known clinical observation for many years. Several previous rodent studies reported that radiation before or immediately after fracture causes alterations in the histology and radiology of the reparative processes . However, all those studies used whole‐body radiation, which limited the local radiation dosage that could be applied and was always accompanied by systematic effects, which primarily affect hematopoiesis and had abscopal effects on radiation‐shielded bones .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous rodent studies reported that radiation before or immediately after fracture causes alterations in the histology and radiology of the reparative processes. (22)(23)(24) However, all those studies used whole-body radiation, which limited the local radiation dosage that could be applied and was always accompanied by systematic effects, which primarily affect hematopoiesis (25) and had abscopal effects on radiation-shielded bones. (26) Therefore, they do not faithfully mimic the clinical scenario of the primarily local problem of a traumatic fracture and ensuing nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…As radiation effects are known to vary for different bone cell types and locations 30,34,35 , we assessed the four sub-volumes separately (Table 2). The applied micro-CT protocol did not significantly affect bone formation and resorption activities in the callus VOIs (DC, DP and FP) from week 5-6 with similar bone volume observed in week 5 and 6 for controls and scanned animals.…”
Section: Resultsmentioning
confidence: 99%
“…So far only few studies have focused on the underlying mechanisms of radiation-induced effects on bone mainly focusing on changes in expression profiles of osteoblast and osteoclast differentiation markers 30,35 . Recently, three consecutive in vivo studies by Chandra et al 36,53,54 showed, that radiation‐induced bone loss 53,54 is mediated via Sclerostin inhibition of osteoanabolic Wnt-signaling 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was demonstrated that SSB damage induced upon VUV irradiation has to date been significantly underestimated in radiotherapy models, which provided an explanation for the discrepancies obtained between theoretical and experimental data [116]. Such high levels of damage obtained upon high-dose radiation will be difficult to repair and might interfere with cell cycle progression, at which point cells undergo programmed cell death [117]. All the above allows to conclude that although AGE is popular, easy and inexpensive method, it should not be used for SSBs quantification.…”
Section: Discussionmentioning
confidence: 99%